Artificial Intelligence in education: What are the opportunities and challenges? - Silva , Altieres de Oliveira; Janes , Diego dos Santos (Review of Artificial Intelligence in Education, 2023)
Objective: The paper aims to explore the integration of Artificial Intelligence (AI) tools in the educational sector. It underscores the urgent need for establishing proper regulations and checks to ensure the ethical and effective use of these tools. Method: The insights are based on a think piece authored by UNESCO Assistant Director-General for Education, Stefania Giannini. Data was collected through a global survey involving over 450 educational institutions, including schools and universities. Results: A mere 10% of the institutions surveyed have formulated policies or guidelines concerning the deployment of generative AI. The scrutiny for validating textbooks is found to be more stringent than the introduction of generative AI tools in educational settings. Criteria for textbook evaluations encompass content accuracy, relevance to teaching, age suitability, cultural and social appropriateness, and protection against biases. Conclusions: The paper suggests that educational institutions should not be solely dependent on AI corporate entities for setting regulations. While education continues to be a profoundly human endeavor, the surge of digital tools during the COVID-19 crisis underscored the academic and societal challenges students encounter in the absence of human touch. There's a risk that generative AI might diminish the significance of educators and pave the way for increased automation in the educational domain. Addressing the prevailing challenges in education necessitates investments in both schools and educators, rather than just technology. Practical Implications: It's imperative for education ministries to join forces with other regulatory bodies, particularly those overseeing technological advancements, to assess and approve AI tools. UNESCO is at the forefront of global dialogues with stakeholders and is in the process of framing policy guidelines on the use of generative AI in education. UNESCO's 'Recommendation on the Ethics of Artificial Intelligence', released in November 2021, accentuates the principles of safety, inclusivity, diversity, transparency, and excellence.